The Influence of Organizational Culture and Work Motivation on the Work Commitment of State High School Teachers in the Mentawai Islands Regency - Rafikah Bestri; Nellitawati; Jasrial; Sufyarma M (International Journal Of Humanities Education and Social Sciences (IJHESS), 2022)
Based on the results of pre-survey observations in the field, it shows that the teacher's work commitment is still low in carrying out his duties. Low teacher work commitment automatically affects teacher discipline in carrying out their duties. The results of the recapitulation of attendance data for the even semester of the 2021/2022 school year Branch Office of Education Region VIII West Sumatra Province shows that 7 out of 14 public schools have a teacher attendance rate in carrying out assignments at school below 97% of active working days for 131 days in six months, the number the lowest was in SMA Negeri 1 Siberut Barat, namely 87%. This means that 50% of Mentawai Islands State Middle School teachers have low work commitment. This is thought to be related to unfavorable organizational culture and low work motivation. Therefore it is necessary to conduct more in-depth research to test the existence of this problem. This study aims to find and reveal the influence of organizational culture and work motivation on the work commitment of public high school teachers in Mentawai Islands District. The population in this study was all teachers of SMA Negeri Kabupaten Kepulauan Mentawai 209. The research sample was 55 people taken using the Stratified proportional random sampling technique based on strata of group and length of service. The research instruments used are assessment scales and questionnaires of Likert Scale models that have been tested for validity and reliability. The research data were analyzed by correlation and regression techniques. The results of data analysis show that: (1) organizational culture affects work commitment as much as 23%, (2) work motivation affects work commitment as much as 71.0%, (3) organizational culture and work motivation together affect work commitment as much as 86.6%. The achievement level of organizational culture score of 78.26% is in the sufficient category, the level of achievement of the work motivation score of 78.68% is in the sufficient category and the achievement of the teacher's work commitment score of 79.65% of the ideal score is also in the sufficient category. The findings above imply that teachers' work commitment is significantly influenced by organizational culture and work motivation. Beyond other factors. Therefore it can be concluded that improving organizational culture in a better direction and increasing work motivation becomes high, it will increase the teacher's work commitment also becomes higher